2019
DOI: 10.1167/iovs.18-25617
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Mesenchymal Stem Cells Modulate miR-126 to Ameliorate Hyperglycemia-Induced Retinal Inflammation Via Targeting HMGB1

Abstract: Exosomes derived from mesenchymal stem cells modulate miR-126 to ameliorate hyperglycemia-induced retinal inflammation via targeting HMGB1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 35 publications
3
113
0
3
Order By: Relevance
“…This finding is further supported by an experiment on MSC‐derived exosomes to examine their influence on hyperglycemia‐induced retinal inflammation. The results indicated that the administration of MSC‐derived exosomes effectively reversed the inflammation induced by hyperglycemia in diabetic rats (Zhang, Wang, & Kong, ). Our data clearly indicate that exosomes derived from osteogenically differentiating MSCs at early stages have an effective inflammation‐regulatory ability.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is further supported by an experiment on MSC‐derived exosomes to examine their influence on hyperglycemia‐induced retinal inflammation. The results indicated that the administration of MSC‐derived exosomes effectively reversed the inflammation induced by hyperglycemia in diabetic rats (Zhang, Wang, & Kong, ). Our data clearly indicate that exosomes derived from osteogenically differentiating MSCs at early stages have an effective inflammation‐regulatory ability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in human retinal endothelial cells treated with high glucose, HMGB1siRNA reduced oxidative stress and cellular apoptosis. In addition, a recent study demonstrated that exosomes derived from mesenchymal stem cells overexpressing miRNA-126, an endothelial specific miRNA that mediates inflammation, suppressed HMGB1 expression and NF-kB and NLRP3 inflammasome activity in human retinal endothelial cells [136,137]. Finally, protein kinase A (PKA) seems to inhibit cytoplasmic HMGB1 [137].…”
Section: Hmgb1 and Diabetic Retinopathymentioning
confidence: 99%
“…They found that the implanted MSC-Exo efficiently delivered miRNA-222 into the retina to prevent the progression of retinal degeneration 122 . Similarly, Zhang et al discovered that human umbilical cord MSC-Exo reduces hyperglycaemia-induced retinal inflammation after intravitreal injection into rabbis with DM 123 . Based on the high efficacy of MSC-Exo for RD control in preclinical trials, a clinical trial intending to evaluate the function of serum exosomal miRNA in the pathogenesis of DR has obtained FDA approval (NCT03264976) and will soon recruit patients 124 .…”
Section: Stem Cell-derived Exosomes For Rd Treatmentmentioning
confidence: 94%